Stress disturbance induced by multiple-well fracturing and its influence on initiation and near-wellbore propagation from infill horizontal perforated borehole. Issue 7 (October 2021) - Zhang, Kuangsheng; Tang, Meirong; Du, Xianfei; Wang, Xiaohua; Zhang, Fengshou; Tang, Jizhou
Abstract: Multiple stage fracturing with multiple pads (MSFMP) is an essential technology for efficient development of unconventional reservoirs, but connecting area of two well pads is still not stimulated. The in-situ stress in the connecting area of well pads would be disturbed after MSFMP, affecting the initiation and near-wellbore propagation of infill horizontal well whose horizontal wellbore deviates greatly from the optimal orientation. Therefore, this paper proposes a method for calculating the stress perturbation caused by MSFMP and then optimizing the perforation parameters of infill horizontal wells in the unstimulated area. The results show that stress disturbance at any position can be calculated based on the stress disturbance model, and then the optimal fracturing interval is obtained in the middle unstimulated area. Appropriate perforation parameters can significantly decrease the complexity of near-wellbore fractures.